Araştırma temelli öğretim ve bilimsel tartışma yönteminin ilköğretim öğrencilerinin asitler ve bazlar konusunu öğrenmesi üzerine etkilerinin karşılaştırılması - Kaya, Bahar (My University, 2009)
With the inclusion of “development of science process skills” among the chief goals of the science education, the “science” concept began to be dealt with as a “process” in addition to being “knowledge” (Ari, 2008). Studies conducted revealed that traditional teaching is unsuccessful in teaching acids and bases. (Sinan, 2007; Bilgin and Geban, 2004; Sezer and Tokcan, 2003; Bol, Nunnery and Whicker, 1997). Above all these, it can be said that skill acquisition, which is the aim of teaching, cannot be achieved through traditional instruction-based experiments, and that it falls short in acquisition of skills relating to hypothesis formation and testing process, which are among the basic steps of problem solving. Within this framework, inquiry-based education comes into prominence. In-class applications aimed at teaching acids and bases with inquiry-based education have been encountered in literature, but no studies involving use of scientific research with inquiry-based teaching jointly have been encountered. “Acids and Bases” subject, which is among the most important concepts of the high school curriculum, has been the subject of many studies in the literature. Studies conducted show that primary and high school students have typical misconceptions, which are experienced frequently relating to the matter. (Ross & Munby, 1991; Ayas & Ozmen, 1998; Demircioglu, Ozmen & Ayas, 2001; Ozmen, 2004; Demircioglu, Ozmen & Ayas, 2004). On the other hand, although we see many examples of acid and base reactions in our daily lives, students are introduced with scientific information about acids and bases at the eighth grade for the first time. In addition to all these, the fact that the subject of “ACIDS and BASES” allows both development of science process skills and development of students’ active laboratory performance was effective in preference of this subject as the subject matter. It has been seen as a result of the literature review conducted that there are propositions regarding that it would be beneficial if scientific argumentation is included in inquiry-based teaching. Within this context, the literature gap found forms the basis of this study. The purpose of the study is to compare the effects of “Traditional Teaching”, “Inquiry-Based Teaching” and “Inquiry-Based Teaching also including the Scientific Argumentation-Based Teaching” on primary school students’ learning the acids and bases subject and their science process skills. The pre-test and post-test model with control group was used in the study. Applications were carried out with the traditional method in the control group, and constructivist methods in other two experimental groups. The inquiry-based teaching method alone was used in one of the experimental groups, while the inquiry-based teaching along with the scientific argumentation-based teaching method was used in the other. The study was conducted with 99 eighth-grade students. A logical thinking test, science process skills test, and conceptual understanding questionnaire were applied to students before the study. Total of three equivalent teaching groups were formed on this basis. The working groups of students at the laboratory were determined based on the scores of the science process skills test in each teaching group. The groups were formed in such a way to create a heterogeneous structure in terms of science process skills. All groups prepared an experiment report at the end of each experiment, and in the last 15-20 minutes of the lesson with the members of the group. However, the format of experiment report showed differences depending on the teaching method. Following the completion of the application, the conceptual understanding questionnaire, science process skills test, science process skills observation questionnaire and a multiple-choice achievement tests were given to the groups. All these activities were completed in total of two and a half months. The findings of the study show that there is significant difference in favor of post-teaching in terms of pre-test and post-test in all teaching groups in the conceptual understanding test. On the other hand, there is significant difference in favor of post-teaching in experimental groups in terms of science process skills, while there is no significant difference between pre-teaching and post-teaching in the control group. No significant difference was observed between the groups in the post-test scores, when a comparison was made based on the teaching method variant to determine which teaching method provides more effective learning. On the other hand, there is significant difference between the group involving scientific argumentation and the control group in the results of the achievement test consisting of multiple-choice questions. Statistical analyses conducted showed that achievement of male students significantly differentiated from that of female students. Key Words: Constructivism, Chemistry Laboratory, Scientific Process Skills, Inquiry-Based Instruction, Argumentation-Based Instruction, Traditional-Based Instruction.

Fen eğitiminin temel amaçları arasına “bilimsel işlem becerilerinin geliştirilmesi” kazanımının da dahil edilmesiyle birlikte “bilim” olgusu “bilgi” olmanın yanı sıra “süreç” olarak da ele alınmaya başlamıştır (Arı, 2008). Yapılan araştırmalar, asitler ve bazların öğretiminde geleneksel öğretimin başarılı olamadığını ortaya koymaktadır (Sinan, 2007; Bilgin ve Geban, 2004; Sezer ve Tokcan, 2003; Bol, Nunnery ve Whicker, 1997). Tüm bunlardan öte, öğretimin hedefinde yatan beceri ediniminin geleneksel yönergeye dayalı deneyler ile sağlanamadığı, problem çözmenin temel basamakları arasında yer alan hipotez oluşturma ve test etme sürecine ilişkin becerilerin ediniminde yetersiz kaldığı söylenebilir. Bu çerçevede araştırma temelli öğretim ön plana çıkmaktadır. Literatürde araştırma temelli öğretim ile asitler ve bazların öğretimine yönelik sınıf içi uygulamalara rastlanmıştır, ancak bilimsel tartışmanın da araştırma temelli öğretim ile birlikte kullanıldığı herhangi bir araştırmaya rastlanmamıştır. Gerek ilköğretim gerekse lise müfredatının en önemli kavramlarından olan “Asitler ve Bazlar” konusu, literatürde pekçok araştırmaya konu olmuştur. Yapılan araştırmalar ilköğretim ve lise öğrencilerinin konuyla ilgili sıkça yaşanan tipik kavram yanılgılarına sahip olduğunu göstermektedir (Ross & Munby, 1991; Ayas & Özmen, 1998; Demircioğlu, Özmen & Ayas, 2001; Özmen, 2004; Demircioğlu, Özmen & Ayas, 2004). Diğer taraftan günlük yaşamda karşılaştığımız pek çok olayın birer asit-baz olayı olmasına karşın öğrenciler, asitler ve bazlarla ilgili bilimsel bilgiyle ilk defa sekizinci sınıfta tanışmaktadır. Tüm bunlara ek olarak konu seçiminde gerek bilimsel işlem becerilerinin geliştirilmesine gerekse öğrencilerin aktif laboratuar performansının geliştirilmesine imkan sağlaması “ASİTLER VE BAZLAR” konusunun tercih edilmesinde etkili olmuştur. Yapılan literatür taraması sonucunda, araştırma temelli öğretim içerisinde bilimsel tartışmanın yer almasının faydalı olacağına dair önerilere rastlanmıştır. Bu bağlamda belirlenen literatür boşluğu araştırmanın temelini oluşturmuştur. Araştırmanın amacı “Geleneksel Öğretim”, “Araştırma Temelli Öğretim” ve “Bilimsel Tartışmaya Dayalı Öğretimi de içeren Araştırma Temelli Öğretim” yöntemlerinin, ilköğretim öğrencilerinin; asitler ve bazlar konusunu öğrenmeleri, bilimsel işlem becerileri ve bilimsel süreç becerileri üzerindeki etkilerini karşılaştırmaktır. Araştırmada kontrol gruplu öntest-sontest deneysel desen kullanılmıştır. Uygulamalar kontrol grubunda geleneksel yöntemle; diğer iki öğretim grubunda yapılandırmacı yöntemlerle yapılmıştır. Deneysel gruplarımızdan birinde tek başına Araştırma temelli öğretim uygulanırken; diğerinde araştırma temelli öğretim bilimsel tartışma temelli öğretim ile birlikte kullanılmıştır. Araştırma sekizinci sınıfta okuyan 99 öğrenci ile yürütülmüştür. Araştırma öncesi öğrencilere mantıksal düşünme yeteneği testi, bilimsel işlem becerileri testi ve kavramsal anlama anketi uygulanmıştır. Anket ve Testlerin analizleri eşdeğer üç öğretim grubunu ortaya koymuştur. Laboratuar çalışma grupları öğrencilerin bilimsel işlem beceri testinden aldıkları puanlar doğrultusunda oluşturulmuştur. Gruplar, bilimsel işlem becerileri açısından heterojen yapıda olacak şekilde oluşturulmuştur. Tüm gruplar deney sonunda ve dersin son 15-20 dakikasında grup üyeleri ile birlikte deney raporu hazırlamıştır, ancak deney tutanağı formatı öğretim yöntemine göre farklılık göstermektedir. Uygulama bittikten sonra öğretim gruplarına kavramsal anlama anketi, bilimsel işlem becerileri testi, bilimsel süreç becerileri gözlem anketi, çoktan seçmeli başarı testi uygulanmıştır. Bu etkinlikler toplam iki buçuk ayda tamamlanmıştır. Araştırma bulguları, kavramsal anlama testinde tüm öğretim gruplarında öntest-sontest açısından öğretim sonrası lehine anlamlı fark oluşmuştur. Öte yandan bilimsel işlem becerileri açısından deney gruplarında öğretim sonrası lehine anlamlı fark ortaya çıkarken; kontrol grubunda öğretim öncesi ile sonrası arasında anlamlı fark oluşmadığı belirlenmiştir. Hangi öğretim biçiminin daha etkili bir öğrenme sağladığı konusunda öğretim yöntemi değişkenine göre karşılaştırma yapıldığında sontest skorlarına için gruplar arasında anlamlı fark ortaya çıkmamıştır. Diğer taraftan çoktan seçmeli sorulardan oluşan başarı testinde bilimsel tartışma içeren öğretim grubuyla kontrol grubu arasında anlamlı bir fark ortaya çıkmıştır. Yapılan istatistiki analizler erkeklerin başarısının kızların başarısından anlamlı şekilde farklılaştığını ortaya koymuştur. Yapılandırmacılık, Kimya Laboratuarı, Bilimsel İşlem Becerileri, Araştırma Temelli Öğretim, Bilimsel Tartışma Temelli Öğretim, Geleneksel Öğretim
Keywords: Araştırma Temelli Öğretim; Bilimsel İşlem Becerileri; Bilimsel Tartışma Temelli Öğretim; Geleneksel Öğretim; Kimya Laboratuarı